2011
DOI: 10.4314/ajpsy.v14i1.65466
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and problem drinking in South Africa: findings from a national population-based survey

Abstract: This study formed part of the South African National HIV, Incidence, Behaviour and Communication (SABSSM) 2008 survey, which included questions assessing the extent of alcohol use and problem drinking among South Africans. Method: A multistage random population sample of 15 828 persons aged 15 or older (56.3% women) was included in the survey. Alcohol use was assessed using the Alcohol Use Identification Test (AUDIT). Tabulation of data for different age groups, geolocality, educational level, income, and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
169
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 23 publications
(36 reference statements)
28
169
11
Order By: Relevance
“…This was demonstrated in this study as majorities (71.0%) of the caregivers were unemployed; the households were relying on pension funds and child grants as a source of income. This was also reported by a study conducted in the Western Cape whereby 66.0% of the caregivers depended on grants for economic survival [24]. As indicated that pension funds and grants are the main source of income, most of the households (27%) receive income of less than ZAR1000 (1 USD).…”
Section: Socio-demographic Background and Health Statussupporting
confidence: 63%
“…This was demonstrated in this study as majorities (71.0%) of the caregivers were unemployed; the households were relying on pension funds and child grants as a source of income. This was also reported by a study conducted in the Western Cape whereby 66.0% of the caregivers depended on grants for economic survival [24]. As indicated that pension funds and grants are the main source of income, most of the households (27%) receive income of less than ZAR1000 (1 USD).…”
Section: Socio-demographic Background and Health Statussupporting
confidence: 63%
“…In terms of population groups, the coloured population had the highest risk for dual substance use, as has been reported in previous studies performed in SA. [34,35] Furthermore, congruent with previous findings, [1][2][3][4] TB retreatment patient status and non-adherence to anti-TB medication were associated with conjoint alcohol and tobacco use. However, unlike in other studies, [7,8,[10][11][12][13][14][15][16][17] there was no association between mental problems, PTSD, poor quality of life and alcohol and tobacco use.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of conjoint alcohol and tobacco use was 6.16 times higher among male than female patients. This finding conforms with previous studies in SA, [34] but is contrary to the results of a study conducted in Brazil. [33] In agreement with other studies, [14] a lower education level and greater degree of poverty were associated with conjoint alcohol and tobacco use.…”
Section: Discussionsupporting
confidence: 83%
“…Illicit drug use and excessive use of alcohol before sexual intercourse have been found to be associated with risky lifestyles and lack of condom use (Parry et al, 2005;Kalichman et al, 2007;Peltzer et al, 2011;Seth et al, 2011). Studies relating condom use to factors such as knowledge of how to use a condom and knowledge of STI transmission (Eggers et al, 2014), and to HIV-related knowledge (Villar-Loubet et al, 2013), suggest that HIV knowledge may be an important predictor of sexually risky behaviour in the South African context (Scott-Sheldon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%